Sintering of c-BC2N, Solid Solutions of Metallic Phases Particles with the Additives of Oxide Components and NiCr at Ultra-High Load and Temperature of Spark-Plasma Sintering, High Compaction Pressure During the Explosive Method - Hmelov, A. V. (Refractories and industrial ceramics, 2024)
The article shows the effect of an ultra-high pressing load of 1,20 GPa at 1800°C during spark plasma sintering, compaction pressure of 2,30 GPa at 1260°C during the explosive sintering of the particles of solid solutions of ceramic and metallic phases with the additive of oxide powders mixture, NiCr on the phase composition, microstructure, grain size of the crystalline phases, relative density, linear shrinkage, microstructural features of the boundary layers, microcrack paths, physico-mechanical properties of mullite– c -ZrO 2 – c -BC 2 N–NiCr–V–Mo–Zr–W and mullite– c -ZrO 2 – c -BC 2 N–NiCr–Cr–Mo–Nb–Ta. Spark-plasma sintered c -ZrO 2 at pressing load 35 MPa and temperature 1400°C, g -BC 2 N at pressing load 60 MPa and temperature 1600°C show evoluted crystallization of the c -ZrO 2 and g -BC 2 N phases, respectively, crystalline, uniform, dense microstructures. Samples sintered by the spark-plasma method at an ultra-high pressing load of 1,20 GPa at 1800°C show evoluted mullitization, crystallization of c -ZrO 2 , c -BC 2 N, NiCr, β-V, Mo, W, Zr, β-Cr, Mo, Nb, Ta phases, more crystalline, more uniform and more densely sintered microstructures, variously dispersed grains of the crystalline phases. Samples sintered by both methods differ by the relative density, linear shrinkage, density, uniformity, width, path and moving microcracks across these boundary layers, crack resistance and values of physico-mechanical properties.